PEDAGOGICAL-PSYCHOLOGICAL FEATURES OF DEVELOPMENT OF STUDENTS' PROFESSIONAL AUDITORY ABILITY BY MEANS OF INFORMATIONAL EDUCATIONAL RESOURCES - Jumayeva Gulkhan Amrullayevna (Web of Journals Publishing, 2024)
The educational system of Uzbekistan strives to create an educational model that meets modern global requirements and includes innovative approaches. Development of students' professional auditory skills is important for their future professional activities. Information and educational resources, including audiovisual materials, interactive programs and online platforms, play an important role in this process. This article analyzes the pedagogical and psychological features of the development of students' professional auditory ability.
Keywords: Professions, professional auditory ability, pedagogical-psychological features, audiovisual materials, interactive programs, online platforms.